The impact of smallholder farmers’ participation in avocado export markets on the labor market, farm yields, sales prices, and incomes in Kenya - Amare, Mulubrhan; Mariara, Jane; Oostendorp, Remco; Pradhan, Menno (Elsevier, 2019)
Smallholder producers in sub-Saharan Africa are often unable integrate into markets and access high-value opportunities by effectively participating in global chains for high-value fresh produce. Using data from a survey of large avocado farmers in Kenya, this study examines the determinants and impacts of smallholder-producer participation in avocado export markets on labor inputs, farm yields, sales prices, and incomes, using a switching regression framework to control for selection effects. We found that farmers who participate in export markets differ significantly from nonparticipating farmers: They are older, have somewhat larger farms, have received more training, and own more avocado trees of the Hass variety, the type favored in export markets. Living near a well-functioning avocado farmers’ group is also positively associated with participation in export markets. Participation in avocado export markets will have positive impacts on incomes, revenues, prices, and labor inputs. However, there is an offsetting effect in terms of higher prices and lower volumes, reflecting the stricter quality requirements of export markets. Applying a decomposition analysis, we found that not only differences in endowment sizes, but also differences in returns from endowments in export versus domestic markets, are key to understanding differences in yields, revenues, sales prices, and labor inputs. This suggests that policymakers should not only focus on resource accumulation for farmers, but also pay attention to the inclusiveness of export market participation for smallholder farmers.